Improving magnetic gear overload torque with cage rotor bars - Ackay, Yusuf; Cox, Tom; Costabeber, Alessando (2017)
This paper introduces a coaxial magnetic gearbox with a new high-speed rotor configuration. The proposed configuration optimizes magnet volume and employs cage rotor bars in the high-speed rotor. The resulting proposed gear improves torque performance at overload condition, and utilises 5% less magnet volume in the high¬speed rotor.